Influence of Yarn Count and Cover Factor on Mechanical, Comfort, Aesthetic and Hand Properties of Ladies' Summer Apparel Fabrics. Issue 11 (2nd November 2021) - Iftikhar, Fatima; Ali, Zulfiqar; Hussain, Tanveer; Nazir, Ahsan; Adolphe, Dominique C.
ABSTRACT: Fine cotton fabrics are extremely popular for ladies' summer apparel in the Sub-continent, the Middle East and those parts of the world which are known for hot and humid summer seasons. The purpose of this study was to investigate the mechanical, comfort, and hand properties of fine cotton fabrics by systematically varying the fabric cover factor using two of the most commonly used yarn counts. After undergoing the same pre-treatment processes, fabric test results revealed improvement in fabric wrinkle recovery, smoothness, and resilience with increase in cover factor values from 21 to 26, while deterioration in fabric tear strength, air permeability, moisture management capability, drapability, and softness. It was also revealed that when fabric tear strength and resilience is a priority, production of a specific cover-factor fabric with coarser yarn count gives better results, whereas for better wrinkle recovery, drapability, smoothness, softness, moisture management capability, and air permeability, production of the same cover-factor fabric with finer yarns gives more desirable results.